Regional difference of attenuation of radio waves within Antarctic ice sheet - Ohmae, Hirokazu; Nishio, Fumihiko; Ishikawa, Masao; Katsushima, Takayoshi; Takahashi, Shuhei (1984)
P(論文) The attenuation of radio waves within the ice sheet is caused by absorption loss due to dielectric and electric properties of ice and geometric loss due to spreading of radio waves. The dielectric structure of the ice sheet can be derived by estimating the attenuation. This estimation is useful for the design of the future radio echo sounder. The inland traverse party of the 23rd Japanese Antarctic Research Expedition in 1982 measured an ice thickness by radio echo sounding which operated on 60MHz. Calculations of the attenuation rate of radio waves were made by reading the rate of decrease of the strength of internal echoes on the photographs of the A-scope display records. Values of the attenuation coefficient (dB/100m) in the present study change between about 1.2 and about 3,and become smaller with increase of surface elevation of the ice sheet. But the attenuation coefficient in the bare ice field, the Meteorite Ice Field, around the Yamato Mountains is remarkably high. The regional difference of the attenuation coefficient is caused mainly by the temperature distribution with depth in the ice sheet. But it is considered that the high value of the effective attenuation coefficient in the bare ice field is due to not only different temperature distribution but also different dielectric properties of the bare ice. departmental bulletin paper